STRATEGI KEBUDAYAAN: PENYEBARAN ISLAM DI JAWA - Muchammad Ismail (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2013)
This article reveals the Walisongo’s role as the Javanese’s Islamicscholars who spread out Islam in Java Island. Their teaching has manysocial contributions especially on the messages that were taught by theJavanese Islamic scholars. the preaches contain a series of cultural symbolswhich is basically reflects the social changes.The descriptive methodis used to describe the messages which are implicitly and explicitly lie attheir language. The sociology and culture analysis is not only intended torevealing the meaning of the symbols but also to find out the structure ofthe language.